Diabetic Ketoacidosis Updates: Titratable Insulin Infusions and Long-Acting Insulin Early - Justin Kinney; Oshin Baroi; Mania Gharibian (Critical Care Research and Practice)
Background. To compare a titratable insulin infusion order set (vs. nontitratable) and early administration of long-acting insulin in adult patients with diabetic ketoacidosis (DKA). Methods. Single health system, retrospective study of adult patients admitted to the intensive care unit (ICU) for DKA. The primary outcomes were insulin infusion duration and ICU/hospital length of stays (LoS). Secondary outcomes included ICU/hospital survival, hypoglycemia, and hypokalemia. Results. 151 patients were included in the titratable versus nontitratable insulin infusion comparison. Patients treated with the titratable insulin had shorter hospitalization (6.4 vs. 10.4 days, p=0.03) and reduced the number hypoglycemic events by over half (20.6% vs. 46.0%, p<0.01). 110 patients were identified to compare overlapping a long-acting insulin for more than 4 h with the insulin infusion versus the standard 1-2 h overlap. Patients who received the insulin early spent over 18 h longer on the infusion (p<0.01). Conclusions. A titratable insulin infusion added to the institutional DKA order set was associated with fewer days in the hospital and a significant reduction in hypoglycemic events. Furthermore, overlapping the long-acting insulin earlier with the insulin infusion early showed no benefit and could potentially be worse than the standard overlap.